Advances in Human Factors in Communication of Design Proceedings of the AHFE 2018 International Conference on Human Factors in Communication of Design, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Ho, Amic G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book focuses on the emerging role of human factors in understanding, communicating with and engaging users. It reports on innovative approaches, highlighting visuals cues, such as new typographies, geometries and graphics for mobile and computer interfaces. The book also covers image and video processing, user-focused data compression, generative visuals, computational photography, and interactive design. Further topics include creative and empathetic design, human touch in digital graphics and experiential graphics. Based on the AHFE 2018 International Conference on Human Factors in Communication of Design, held on July 21-25, 2018, in Orlando, Florida, USA, this book reports on new findings, best-practices and case studies, providing readers with a fresh perspective and novel insights into the applications of human factors for enhancing the communication of design to users.
Keywords: Engineering design; User interfaces (Computer systems).; Human-computer interaction; Human-machine systems; Computer graphics; Engineering Design; User Interfaces and Human Computer Interaction; Interaction Design; Computer Graphics